Penerapan Game Wordwall untuk Menstimulasi Bahasa Reseptif Anak Usia Dini di TK Al Azhar Jambi - Intan Novriyanti; Intan Chairani; Winda Sherly Utami; Uswatul Hasni; Akhmad Fikri Rosyadi (Al Fitrah: Journal Of Early Childhood Islamic Education, 2026)
Early childhood education plays an important role in supporting children’s development, particularly receptive language skills. Observations at TK Al Azhar Jambi indicated that some children aged 4–5 years still experienced difficulties in actively listening and understanding teachers’ instructions. This study aimed to describe the implementation of Wordwall games in stimulating receptive language development in early childhood at TK Al Azhar Jambi. This research employed a qualitative descriptive method with 11 children aged 4–5 years as research subjects. Data were collected through observation, interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The results showed that Wordwall games improved children’s receptive language skills, indicated by increased listening focus, the ability to understand two simple instructions simultaneously, and the ability to repeat vocabulary during learning activities. Therefore, Wordwall games can be used as an effective learning medium to stimulate receptive language development in early childhood.